Morbidity-bridging metabolic pathways: linking early cardiovascular disease risk and depression symptoms using a multi-modal approach - Koloi, Angela; Rydin, Arja; Milaneschi, Yuri; Lamers, Femke; Bosch, Jos A; Pruin, Emma; van der Laan; Sander W; Mishra, Pashupati P; Lehtimäki, Terho; Kähönen, Mika; Raitakari, Olli T; et al. (Oxford University Press (OUP), 2026)
Aims: Prevalence of cardiovascular diseases (CVDs) and depression is rising globally. Their co-occurrence associates with poorer outcomes, potentially due to shared metabolic pathways. This study aimed to identify metabolic pathways linking depression symptoms and CVD risk factors.
Methods and results: Data from the Young Finns Study (YFS, n = 1,599, mean age 37 ± 5, 54% female) served as input for a network (mixed graphical models). Confirmatory analysis through covariate-adjusted regression was done with UK Biobank (UKB, n = 69,513, mean age 63 ± 7, 64% female). Mendelian randomization assessed causality using genome-wide association studies data. The study examined 52 plasma metabolites measured by nuclear magnetic resonance spectroscopy. Outcomes included depression symptoms (BDI in YFS, PHQ-9 in UKB) and CVD risk factors [systolic/diastolic blood pressure, carotid intima-media thickness (cIMT)]. Mendelian randomization inferred causal links between metabolites and depression or (intermediate markers of) CVD. Two bridge metabolites were identified: glucose linked to sleep pattern (P = 0.034); omega-3 fatty acids (FAs) linked to appetite change (P < 0.001); and both connected to cIMT (both P = 0.002). Mendelian randomization suggested glucose as causal in coronary artery disease (CAD) risk, while omega-3 FAs showed potential causal links to CAD, coronary artery calcification, and cIMT.
Conclusion: This study integrated three statistical techniques and identified two metabolic markers (glucose, omega-3 FAs) connecting depression and CVD on a symptom and risk factor level. The associations, established in a relatively young cohort, were replicated in a predominantly middle-aged cohort and emphasize both the generalizability of the findings across different populations and value of symptom-level analysis in depression and CVD comorbidity research.
Keywords: Cardiovascular diseases; Comorbidity; Depression; Network analysis.